2023
DOI: 10.3390/ijms24065785
|View full text |Cite
|
Sign up to set email alerts
|

The Drp1-Mediated Mitochondrial Fission Protein Interactome as an Emerging Core Player in Mitochondrial Dynamics and Cardiovascular Disease Therapy

Abstract: Mitochondria, the membrane-bound cell organelles that supply most of the energy needed for cell function, are highly regulated, dynamic organelles bearing the ability to alter both form and functionality rapidly to maintain normal physiological events and challenge stress to the cell. This amazingly vibrant movement and distribution of mitochondria within cells is controlled by the highly coordinated interplay between mitochondrial dynamic processes and fission and fusion events, as well as mitochondrial quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 169 publications
0
10
0
Order By: Relevance
“…Overall, Scrib plays a role in maintaining the cell polarity and cell proliferation regulation by blocking the Drp1 and JNK which regulate mitochondrial dynamics, via maintaining the mitochondrial membrane polarity, morphology and oxidative stress. Mitochondria, a dynamic double membrane-bound cell organelles, play crucial role in ATP production, recently emerged as hub for Drp-1 mediated mitochondrial fission protein interactome connective pathways for various diseases [50]. Our results clearly show that upon knockdown of Scrib leads to enhanced Drp-1 mediated disruption of mitochondrial dynamics, which induces enhanced ROS production and cause reduced ATP production leading to increased cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Overall, Scrib plays a role in maintaining the cell polarity and cell proliferation regulation by blocking the Drp1 and JNK which regulate mitochondrial dynamics, via maintaining the mitochondrial membrane polarity, morphology and oxidative stress. Mitochondria, a dynamic double membrane-bound cell organelles, play crucial role in ATP production, recently emerged as hub for Drp-1 mediated mitochondrial fission protein interactome connective pathways for various diseases [50]. Our results clearly show that upon knockdown of Scrib leads to enhanced Drp-1 mediated disruption of mitochondrial dynamics, which induces enhanced ROS production and cause reduced ATP production leading to increased cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 62%
“…These two mitochondrial regulators encode a dynamin-family GTPase, to maintain the mitochondrial morphology and activity [11]. The Drp1 migrates from cytosol to mitochondrial outer membrane (MOM) and forms anoligomeric collar like structure around the mitochondrion and hydrolyzes GTP to execute Drp1 -mediated mitochondrial fission event [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial fission is the process by which a mitochondrion fragmentates into smaller mitochondria. DRP1 is a GTP-hydrolyzing enzyme that plays a crucial role in mediating mitochondrial fission [ 52 , 53 ]. DRP1 and its receptors—mitochondrial fission protein 1 (FIS1), mitochondrial dynamics proteins of 49 and 51 kilodaltons (Mid49/51), and mitochondrial fission factor (MFF)—regulate mitochondrial fission [ 54 ].…”
Section: Mitochondrial Physiology: Focus On Mitochondrial Dynamics An...mentioning
confidence: 99%
“…It was suggested that Fis1/Mid51 PPI results in increased mitochondrial pathological fission ( Zhao et al, 2011 ; VĂĄsquez-Trincado and Schinkel, 2016 ; Liu et al, 2023 ). Moreover, imbalanced mitochondrial dynamics were demonstrated to lead to a number of human pathologies, such as CVDs ( Zerihun et al, 2023 ). Therefore, an inhibitor of this interaction may decrease mitochondrial fission and potentially have therapeutic utility.…”
Section: Introductionmentioning
confidence: 99%